2016
DOI: 10.1111/tan.12855
|View full text |Cite
|
Sign up to set email alerts
|

HLA DRB1/DQB1 alleles and DRB1‐DQB1 haplotypes and the risk of rheumatoid arthritis in Tunisians: a population‐based case–control study

Abstract: Rheumatoid arthritis (RA) is an inflammatory disease, which affects synovial joints, and is influenced by environmental and genetic factors, in particular the human leucocyte antigen (HLA) system. In our study, we investigated the association of HLA class II DRB1 and DQB1 alleles and DRB1-DQB1 haplotypes with RA susceptibility in Tunisian subjects. Therefore, HLA class II low-resolution genotyping was done in 110 RA patients and 116 controls, with a HLA-DRB1*04 high-resolution typing. Our results showed a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Corrected P-values were determined by multiplying individual P-values by the number of comparisons made at the locus level as previously described. [17][18][19] For each variant that was considered significantly associated with our outcomes using this method, multiple logistic regression was then employed to control for potential confounders. Pre-specified clinical variables-age, sex, abbreviated injury scale (AIS) scores for the head, spine, abdomen, and chest, and transfusion requirement-were included in the multiple logistic regression.…”
Section: Discussionmentioning
confidence: 99%
“…Corrected P-values were determined by multiplying individual P-values by the number of comparisons made at the locus level as previously described. [17][18][19] For each variant that was considered significantly associated with our outcomes using this method, multiple logistic regression was then employed to control for potential confounders. Pre-specified clinical variables-age, sex, abbreviated injury scale (AIS) scores for the head, spine, abdomen, and chest, and transfusion requirement-were included in the multiple logistic regression.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies reported the frequency of SS across autoimmune and other rheumatic conditions (Supplementary Table S7, http://links.lww.com/RHU/A253). 12,15,16,[18][19][20][21][24][25][26][27][29][30][31] The frequency of pSS ranged from 1.8% in a cross-sectional study from Morocco reporting data of 944 subjects with diverse autoimmune diseases recruited between 2010 and 2016, 29 to 47.6% in a cross-sectional study from Senegal reporting data of 27 subjects with systemic vasculitides recruited during 1995-2007. 16 Regarding sSS, the frequency in patients with RA ranged from 4.3% in a cross-sectional study conducted in Morocco during 2007-2011 and including 164 patients, 20 to 100% in the aforementioned study from Senegal, which included only 4 RA patients.…”
Section: Frequencymentioning
confidence: 99%
“…However, there are differences in the allelic frequency of certain HLA-DRB1 SE alleles across different populations. For instance, HLA-DRB1*04:01 and HLA-DRB1*04:04 alleles are common in RA patients with Caucasian ancestry, while HLA-DRB1*04:05 allele is common in the Asian population [3,6,7,9,[12][13][14][15]. It is also evident that the overall frequency of HLA-DRB1 SE alleles in Asian populations is lower than in Caucasian populations, despite the similar RA prevalence between these populations.…”
Section: Introductionmentioning
confidence: 99%